Product of two 2F2 Generalized Hyper-geometric Functions and their Special Cases - Poudel, Madhav Prasad; Pahari, Narayan Prasad; Panthi, Dinesh (The Nepali Mathematical Sciences Report, 2024)
A remarkable number of identities have been established related to the product of generalized hypergeometric series in recent years. In the present work, we shall establish certain identities involving the product of two generalized hypergeometric functions. Bailey’s theorem is used to evaluate the particular cases for the product.